LIVER BIOPSY WITH SPINAL (LUMBAR PUNCTURE) NEEDLE-A CHEAPER ALTERNATIVE - Jadoon, Habib Ahmed (Journal of Ayub Medical College Abbottabad, 2000)
Background: Percutaneous liver biopsy is widely used for the diagnosis and management of liver diseases. The aim of this study was to investigate the efficacy and safety of spinal (lumbar puncture) needle for percutaneous liver biopsy. Methods: 100 percutaneous liver biopsies were carried out on 76 male and 24 female patients (ages 16 to 60 years) using size 18 spinal (lumbar puncture) needles. Results: Adequate tissue for histological diagnosis was obtained in 96% with 4% failures. One pass yielded adequate tissue for histological diagnosis in 70%, 2 passes were required in 25% and 5% needed 3 passes. Mean length of tissue obtained per pass was 4 cm. Fragmentation of biopsy specimen occurred in only 10%. The most common complication was procedure related pain, only one patient (1%) had a serious nonfatal haemorrhagic complication. Conclusion: We found spinal needle to be very- economical, safe and efficacious for routine percutaneous liver biopsies. Key Words: Percutaneous liver biopsy. Needle liver biopsy, spinal needle.